Educational Video Materials in Teaching Foreign Languages in the Conditions of Distance Learning - Bezhenar, Iryna; Petrenko, Oksana; Hnatyshena, Iryna; Yemelyanova, Yevgeniya; Muravyova, Irina (My University, 2023)
Economic, political and social changes in the world cause the acceleration of reforming the education system. As a result, an innovative, promising form of organization of the educational process, distance learning, is developing. It opens up wider opportunities for providing educational services. Studying foreign languages in educational institutions at all stages of the educational process is a priority task for the formation of a competitive specialist in the modern labor market. One of the most urgent problems requiring the search for new solutions at the current stage of the educational system development is the need for qualitative improving the methods of teaching foreign languages in educational institutions. The purpose of the academic paper is to clarify the degree, directions and main trends in the scientific study of using educational video materials in teaching foreign languages under the conditions of distance learning, as well as studying certain practical aspects of this issue based on the experience of participants and researchers of the educational process. In the course of the research, analysis, synthesis, induction, and deduction was used to process scientific information. System-structural, comparative, logical-linguistic methods, abstraction, and idealization were applied to study and process data. The research authors conducted the survey in online mode. Based on the research results, the theoretical and practical aspects of applying video tools that can be used in learning foreign languages under the conditions of remote organizing the educational process have been studied.
Keywords: distance learning of foreign languages, methods of teaching a foreign language, video resources for learning a foreign language, optimization of teaching a foreign language